A Device for Children’s Instrumental Creativity and Learning: An Overview of the MIROR Platform - Addessi, Anna Rita (Frontiers in Psychology, 2020)
This article introduces the pedagogical paradigm of reflexive interaction and its application in the field of technology-enhanced learning and musical creativity. The main feature of reflexive interaction is the repetition-variation mechanism: something is repeated and varied during the interaction, through a continual process of imitation and variation. In the context of the MIROR project (EU-ICT Project), we exploited the educational potential of reflexive interaction paradigm and implemented the MIROR platform, an educational device consisting of a set of softwares that implements the reflexive paradigm not only in music improvisation (as was the case for the first interactive reflexive system), but also in the field of music composition and dance. The platform was conceived as a tool to stimulate and develop musical and motor creativity in children, although it can also be used to teach a specific musical instrument. The hypothesis of the MIROR project was that reflexive interaction sustains and promotes the learning and creative expression processes of music and movement. This initial hypothesis, which stemmed mainly from the observation of children who were interacting with the first prototype of IRMS, was subjected to a series of empirical studies conducted within the MIROR project, and was theoretically defined in order to lay out the foundations of the reflexive interaction paradigm and its psycho-pedagogical implications. In this article, an overview of the theoretical framework, methodological approaches, pedagogical concepts, and the results of the empirical studies are introduced, together with the description of the MIROR platform, with the aim to point out the contribution of the reflexive perspective to the field of children’s instrumental learning and creativity.